2003
DOI: 10.1016/s0022-5223(03)00550-6
|View full text |Cite
|
Sign up to set email alerts
|

Early and late stroke after mitral valve replacement with a mechanical prosthesis: risk factor analysis of a 24-year experience

Abstract: Persistent atrial fibrillation was the most significant risk factor for late stroke after mechanical mitral valve replacement. Restoration of sinus rhythm with a maze procedure nearly eliminated the risk of late stroke, whereas neither closure of the left atrial appendage nor therapeutic anticoagulation prevented this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 22 publications
5
50
0
5
Order By: Relevance
“…They found the incidences of new onset of postoperative stroke to be 2.0%, and in 36.5% of these patients group postoperative AF preceded the occurrence of stroke. Bando et al investigated the risk factors for early and late stroke after mechanical mitral valve replacement, and concluded that restoration of sinus rhythm with a maze procedure nearly eliminated risk of stroke [20]. In the present study, late stroke was observed more frequently in patients who developed persistent AF after surgery than in patients who had only temporary AF.…”
Section: Discussionsupporting
confidence: 53%
“…They found the incidences of new onset of postoperative stroke to be 2.0%, and in 36.5% of these patients group postoperative AF preceded the occurrence of stroke. Bando et al investigated the risk factors for early and late stroke after mechanical mitral valve replacement, and concluded that restoration of sinus rhythm with a maze procedure nearly eliminated risk of stroke [20]. In the present study, late stroke was observed more frequently in patients who developed persistent AF after surgery than in patients who had only temporary AF.…”
Section: Discussionsupporting
confidence: 53%
“…Nuestra experiencia muestra que las complicaciones derivadas de ésta prótesis fueron responsables de 19% de la mortalidad alejada de los pacientes. No obstante, la supervivencia alejada de los tres grupos fue muy satisfactoria y coincide con lo encontrado por otros autores 17,30,37 . Concluimos que los factores de riesgo significativos en el resultado del reemplazo valvular mitral son dependientes de las características clínicas del paciente, no del tipo de intervención ni del sistema de salud de origen.…”
Section: Discussionunclassified
“…No randomized controlled trial has shown clear clinical improvements and only some personal series have suggested benefits in stroke or survival (5)(6)(7)(8). But very recent data analysis from the STS database matching 28,739 patient-pairs with and without AF described that surgical ablation was associated with a reduction in mortality and stroke, while an increase in renal failure and the need for pacemaker implantation (9).…”
Section: Why To Treat Af In Mitral Insufficiencymentioning
confidence: 99%